2005
DOI: 10.1111/j.1365-2559.2005.02265.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma arising in the nasal cavity among Japanese

Abstract: Our present study indicates that primary lymphomas arising in the nasal cavity are mostly of NK cell derivation. Our present study also suggests that a small number of cases are derived from NKT-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Soft tissue plasmacytoma has a significant sex-related susceptibility, with a mean male/ female ratio of 2.7. In this study males were more frequently affected, consistent with data previously reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Soft tissue plasmacytoma has a significant sex-related susceptibility, with a mean male/ female ratio of 2.7. In this study males were more frequently affected, consistent with data previously reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 81%
“…It accounts for 1 % of all head and neck malignant tumors. The most common sites of EMPs are the nose, paranasal sinuses, nasopharynx and tonsils, but it can also occur in the gastro-intestinal tract, CNS, urinary bladder, thyroid, testes, parotid gland and lymph nodes [3][4][5][6]. Men are more commonly affected, with a median age at diagnosis of 50-60 years.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,10,13 This may be due to the exclusion of some less bulky nasal cases with limited diagnostic samples from our study. Referral bias is also important since nasal and cutaneous disease may be referred initially to otolaryngology or dermatology centers, 21,22 and the diagnostic material may not be kept after review at the tertiary oncology center. This may also explain the lower incidence of extranasal disease in Japan, which is discordant with previous retrospective series.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal NKTL is more frequent in Asia and Central America, and is relatively rare in the US and Europe [13]. Lymphomas arising primarily in the nasal cavity are mostly of T-cell origin and those in the paranasal sinus are more of B-cell origin [14]. Primary nasal lymphomas are mostly of NK cell origin.…”
Section: Discussionmentioning
confidence: 99%